Chuvas e inundações em Goiânia: dinâmica atmosférica e áreas de risco - Rego, Thalyta Lopes (2015)
Deforestation and waterproofing of various spaces are common procedures in the urbanization process. These processes, with the fact that the valley bottoms are naturally amenable to flooding, can lead to various disorders for the local population. In Goiania, these events are increasingly accompanied by the local media, and the Civil Defense. From this context, this research performs the mapping of floods in the urban area of Goiânia, between 2000 and 2013 and seeks to identify the atmospheric system that causes these events. Thus, we analyzed and specialized reports published in a newspaper whit the highest circulation in the city and Civil Defense servisse reports. Data from the Meteorological Station of Goiânia were organized in rhythmic analysis charts to understand the atmospheric systems active during flood events. The results show that the floods in Goiania occur nearest the central region of the city, except for two points, which are located in the northern region. It was found that in investigated points the houses are very close to the river and urbanization around these points is quite intense. Another point to be highlighted is the decrease of vegetation in the city during the study period. It was noticed that the most active atmospheric system in the flook occurrences in Goiania are the Repercussion of Polar Mass, the Polar Front and the Equatorial Continental Mass with squall lines. We presented some measures to prevent the flooding, based on surveyed bibliographies.